Motives and homotopy theory in logarithmic geometry - Binda, Federico; Park, Doosung; Østvær, Paul Arne (Comptes Rendus. Mathématique, 2022)
This document is a short user’s guide to the theory of motives and homotopy theory in the setting of logarithmic geometry. We review some of the basic ideas and results in relation to other works on motives with modulus, motivic homotopy theory, and reciprocity sheaves.